Deep Learning, Learning Styles, And Creative Economic Behavior: Evidence from Indonesian University Students - Anung Pramudyo; Sharifah Zannierah Syed Marzuki; Victor Novianto (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study examines how learning styles in entrepreneurship education influence students’ creative economic behavior, with deep learning as the guiding framework. Conducted in 2024, the research involved 399 undergraduate students from five public and private universities in Yogyakarta, Indonesia. Using Structural Equation Modeling, the study analyzes the relationships among learning styles, deep learning practices, motivation, and entrepreneurial behavior. The results show that motivation plays a central mediating role, translating students’ knowledge and attitudes into concrete entrepreneurial actions. Deep learning practices, particularly reflective thinking and applied learning, significantly strengthen students’ motivation and, in turn, their creative economic behavior. These findings indicate that entrepreneurship education is more effective when it moves beyond content transmission toward approaches that emphasize critical thinking, personalized learning, and real-world application. Such a shift is consistent with Indonesia’s Merdeka Belajar policy and contributes to broader global education reform agendas, including the Sustainable Development Goals, by promoting inclusive and innovation-oriented learning environments.